STUDI PENGGUNAAN METODE PENELITIAN KUANTITATIF DAN ANALISIS STATISTIKA PADA SKRIPSI MAHASISWA IAIN PURWOKERTO - Rahmini hadi (IAIN Purwokerto, 2015)
Abstract: During the period 2010-2012 munaqasyah, only 10% of 300 students IAIN Purwokerto thesis were using quantitative research methods. There are 6 forms inconsistency use quantitative research methods, namely (a) inconsistencies in the logic and the application of research variables; (B) no theory or proposition underlying the research hypothesis; (C) the possibility of bias due to a mismatch indicator variable of data research with the establishment survey respondents; (D) the inaccuracy of determining sampling techniques; (E) do not test the validity and reliability of research instrument; and () the inaccuracy of determining validity test techniques. There also inaccuracies on instruments choices and the results of statistical analysis techniques, namely:(a) incompatibility with the scale of measurement variables selected statistical techniques; (B) a mismatch purposes of research or form research hypotheses with statistical techniques were selected; (C) non-conformity data source defined by the selected statistical techniques; (D) the inappropriateness of interpreting the results of statistical analysis. Keywords: Quantitative Research Methods, Statistics Analysis.